Peroral Endoscopic Myotomy for Esophageal Achalasia by HybridKnife: A Case Report - Ping-Hong Zhou; Ming-Yan Cai; Li-Qing Yao; Yun-Shi Zhong; Zhong Ren; Mei-Dong Xu; Xin-Yu Qin (Case Reports in Gastrointestinal Medicine)
This paper presented a case of esophageal achalasia treated by peroral endoscopic myotomy with HybridKnife and discuss the feasibility and the possible advantages of using it.